How Effective is ESD Training for University Lecturers? - Hemmer, Ingrid; Döpke, Marie; Koch, Christoph; Peitz, Anna (Journal of Geography Education, 2023)
In order to implement ESD in the curricula of higher education institutions, ESD training for university lecturers is indispensable. Based on competency models, this article introduces an exemplary training and describes, explains, and discusses the results of the empirical review of its effectiveness. The results show that the training of the participants in the field of professional knowledge, especially in concept knowledge, achieved significant increase. Non-cognitive facets also experienced an increase; however, this only proved to be significant for individual items.